Características de demanda e probabilidade de conclusão dos cursos do Programa Juventude Digital da Prefeitura de Fortaleza - Leitão, Renan Damasceno (2024)
The Digital Youth Program was established by law no. 11,172 of October 13, 2021, and aims to promote the effective digital and productive inclusion of young people through the offering of free courses in several sub-areas (called tracks) of the so-called market digital, such as programming, web design, data analysis and marketing. The program seeks to give priority to young people who have graduated from or enrolled in public schools, while at the same time demanding that young people have an interest in the area, basic knowledge, and availability of time, which can be limiting factors to effective participation and completion of courses. This work will investigate the demand characteristics of the program and the probabilities of students completing their respective courses. For this purpose, it uses a base of microinformation from the program of 6,870 students who signed up for various courses in 2021 and 2022, and of which it was possible to differentiate between those who only signed up, those who actually attended, and of those, those who earned certificates of conclusion. Using multivariate Logit models, the characteristics of students and courses that affect the probabilities of effective participation and completion were investigated in an exploratory manner. Among the main results was a demand profile of students with lower declared income, but with an average age and higher education than during school. It was also found that the models of participation (presence) and completion have different determinants, and that among these, work and lower education are factors that make it difficult to complete the courses.